Sviluppo urbano e politiche per la qualità della vita - Nuvolati, Giampaolo (Studi e saggi, 2018)
Today's society appears increasingly vulnerable, uncertain, complex and ambiguous. In this context, there is an increased need to create efficient and effective ecosystems to locally promote the quality of life and social innovation. The volume offers an excursus of the main innovative practices and policies used within urban development. Each essay explores an area of interest (quality of life, social innovation and sharing economy, smart city, urban mobility, new workplaces, shared living, eHealth, urban security, youth and tourism, food policy, didactic innovation and shared administration) offering a reference overview for the study, design and implementation of new intervention strategies and public policies. This text is aimed at students, teachers and operators working in different positions within the social sectors.